The reliability and validity of measurements of human dental casts made by an intra-oral 3D scanner, with conventional hand-held digital callipers as the comparison measure. (September 2017) - Rajshekar, Mithun; Julian, Roberta; Williams, Anne-Marie; Tennant, Marc; Forrest, Alex; Walsh, Laurence J.; Wilson, Gary; Blizzard, Leigh
Highlights: The use of intra-oral 3D scanners in forensic investigations has been proposed. Reliability and validity of measurements of human dental casts has been assessed. The intra-oral 3D scanner is a reliable and valid method for measuring features of 3D dental casts. This technique may be used for recording and accurately measuring dental features. Abstract: Aim: Intra-oral 3D scanning of dentitions has the potential to provide a fast, accurate and non-invasive method of recording dental information. The aim of this study was to assess the reliability of measurements of human dental casts made using a portable intra-oral 3D scanner appropriate for field use. Method: Two examiners each measured 84 tooth and 26 arch features of 50 sets of upper and lower human dental casts using digital hand-held callipers, and secondly using the measuring tool provided with the Zfx IntraScan intraoral 3D scanner applied to the virtual dental casts. The measurements were repeated at least one week later. Reliability and validity were quantified concurrently by calculation of intra-class correlation coefficients (ICC) and standard errors of measurement (SEM). Results: The measurements of the 110 landmark features of human dental casts made using the intra-oral 3D scanner were virtually indistinguishable from measurements of the same features made using conventional hand-held callipers. The difference of means as a percentage of the average of the measurements by each method ranged between 0.030% and 1.134%. The intermethod SEMs ranged between 0.037% and 0.535%, and the inter-method ICCs ranged between 0.904 and 0.999, for both the upper and the lower arches. The inter-rater SEMs were one-half and the intra-method/rater SEMs were one-third of the inter-method values. Conclusion: This study demonstrates that the Zfx IntraScan intra-oral 3D scanner with its virtual on-screen measuring tool is a reliable and valid method for measuring the key features of dental casts.